Temporary teachers: resilience and welfare promotion - La Marca, Alessandra; Festeggiante, Marcello; Schiavone, Sabrina (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2015)
In recent years, resilience has been object of studies and reflections within the national and international scientific community. Free from an abstract theoretical context, resilience has now become a work praxis and a methodology for all professions. The theoretical model usually adopted defines resilience as the ability to face stressful events, overcome them and continue to grow by increasing one’s own resources with a consequent positive reorganization of life. Our survey aimed at analyzing and measuring the level of resilience of a group of 543 temporary sicilian teachers. We tried and tested their ability to activate useful resources to withstand a common specific and difficult situation (that is the achievement of the teaching qualification) and their ability to adopt coping and appraisal strategies starting from resilient qualities and allowing the successful resolution of critical events. The instrument we used for our survey was the questionnaire of RPQ by Laudadio, Mazzocchetti and Pérez (2011), which offered the opportunity to assess the different components of resilience and has allowed us to obtain various information on personal, emotional and behavioral resources to which resilient teachers appeal in critical and stressful situations. The final discussion of the results contains some directions for future researches related both to the theory and practice of resilience with teachers.